Development and evaluation of QR-coded drug-loaded or dispersible film using 2D inject technology - Acedera, Jude Benedick P.
This study explores the development and evaluation of ODFs loaded with amlodipine via 2D inkjet printing technology. This approach offers a precise method for personalized medicine, enabling customized drug delivery. A quantitative and experimental design was employed to optimize hydroxypropyl methylcellulose (HPMC) film-former substrate formulations (5, 7.5, and 10% w/v). The drug-loaded ink was printed directly onto a newly developed porous substrate to achieve targeted doses of 2.5 mg and 5 mg, which were achieved by printing multiple layers. Each printed film was assayed to confirm the printed dose. While the 5% HPMC formulation proved unsuitable, both 7.5% and 10% concentrations initially achieved successful printing and handling characteristics. However, the 10% HPMC formulation demonstrated superior handling capacity during multiple printing cycles for achieving higher doses. In vitro dissolution studies revealed rapid drug release from both substrate formulations, passing the USP criteria for amlodipine dissolution. However, the 10% HPMC formulation displayed slower drug release than the 7.5% formulation. Additionally, the stability of the ink was assessed after three weeks within the inkjet printer cartridge. Results indicated minimal degradation of the amlodipine, demonstrating the formulation's suitability for long-term storage within the printing system. Overall, findings support the potential of 2D inkjet printing technology for the development of personalized ODFs with precise dosing, rapid drug release, and formulation stability within the printing system. Further research exploring a broader range of drugs and formulations can solidify inkjet printing as a prominent tool for personalized medicine.